PENENTUAN KADAR SENYAWA ORGANIK MATA AIR DI DESA PESEDAHAN, KARANGASEM SECARA PERMANGANOMETRI - I Made Arya Wirya Atmaja; I Made Oka Adi Parwata; Putu Gede Subhaktiyasa (Stikes Wira Medika Bali, 2017)
Introduction: Water is the main component / important for living things, so its quality and quantity needs to be maintained. Similarly, the springs in the Pesedahan Village, Manggis District, Karangasem Regency that gives an important influence for the community’s activities there.Water quality decline to a certain level caused by one of the organic compounds contamination. The decrease of water quality to a certain level is caused by one of the organic compounds. Method: This research is a quantitative research. The purpose of this research is to determine and analyze the level of organic compound spring in Pesedahan Village, Manggis Subdistrict, Karangasem Regency. The research was conducted on 5 springs in the location, each taken 2 L as sample. Result: The result of the research by permanganometri result showed that the data of organic compound samples 1, 2, 3, 4, and 5 sequentially in mg / L were 8,2581, 8,8481, 11,0178, 9,8381 and 6,6781, respectively With Permenkes R1 No.492 / Menkes / Per / IV / 2010 found that the organic compound of sample 3 exceeded the maximum limit, while the other four samples were below maximum. Discussion: For that it is advisable for the community to maintain the safety of water springs, one of which cleans the area of ​​the spring, and does not dispose of waste around the springs location.